2004
DOI: 10.1007/s00421-003-1015-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drinking tea at high altitude on hydration status and mood

Abstract: The effect of drinking tea on hydration status and mood was studied in nine male and four female members of expeditions based at Mt. Everest base camp at an altitude of 5,345 m. Whilst exposed to altitude-cold diuresis, participants were subjected to a crossover experimental design comprising two 24-h dietary interventions. In the "tea" condition, hot brewed tea formed a major part of fluid intake, whereas in the "no-tea" condition tea was excluded from the diet. Subjects were prohibited in both cases from con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…This position was confirmed by a study (Scott et al, 2004) that compared regular tea consumers with non-consumers in a crossover study of fluid balance during extreme physiological stress. Participants were members of an expedition at Mount Everest Base Camp.…”
Section: Hydrationmentioning
confidence: 70%
See 1 more Smart Citation
“…This position was confirmed by a study (Scott et al, 2004) that compared regular tea consumers with non-consumers in a crossover study of fluid balance during extreme physiological stress. Participants were members of an expedition at Mount Everest Base Camp.…”
Section: Hydrationmentioning
confidence: 70%
“…Evidence that tea had no diuretic effect unless the caffeine content of tea consumed at one sitting exceeded 300 mg. Maughan and Griffin (2001) No evidence that tea was dehydrating at altitude. Scott et al (2004). Dental health Little evidence to support effect of tea on plaque inhibition.…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…However, sedation ratings were decreased by caffeine irrespective of vehicle, representing a failure to replicate earlier findings (128) . In a naturalistic study at high altitude, Scott et al (129) demonstrated that tea drinking was associated with lower fatigue ratings in regular tea drinkers. More recently De Bruin et al (130) described two randomised, controlled trials of black tea as compared with placebo tea.…”
Section: Tea (Camellia Sinensis)mentioning
confidence: 99%
“…Examples include measuring urine specific gravity or urine osmolality (Grandjean et al, 2003;Manz & Wentz, 2005;Martin et al, 2006;Popowski et al, 2001;Scott, Rycroft, Aspen, Chapman, & Brown, 2004;Wakefield et al, 2002), urine volume (Grandjean et al, 2003;Scott et al, 2004;Shirreffs et al, 2004), or urine color (Armstrong, 1994;Fletcher, Slaymaker, Bodenham & Vucevic, 1999;Mentes, Wakefield, & Culp, 2006;Scott et al, 2004;Wakefield et al, 2002). There are gender and race/ethnicity differences in some urinary indices (e.g.…”
Section: Hydration Statusmentioning
confidence: 99%
“…Yet, evidence which supports the contribution of caffeinated and alcoholic beverages towards hydration and as a source of water has been provided in the literature (Grandjean et al, 2000;Kant, Graubard, & Atchison, 2009;Scott et al, 2004;Vivanti et al, 2010). Grandjean et al (2000) reported no change in hydration status when the TWI including caffeinated beverage intake from habitual caffeine consumers was compared to TWI from non-caffeine consumers.…”
Section: Water Balancementioning
confidence: 99%